2DAMP: the novel of (2D)-Aminoethyl Methacrylate Perovskite for ammonia gas sensor - Adli, Hasyiya Karimah; Mat Yunin, Muhamad Yuzaini Azrai; Mohd Adenam, Norfatihah; Ab Ghani, Hadhrami (Universiti Teknologi MARA, Kedah, 2023)
2DAMP is a novel class of materials based on (2D)-Aminoethyl Methacrylate Perovskite with better stability and great potential for the ammonia gas sensor. 2DAMP is introduced as a strategy to promote and explore a sustainable green economy. Malaysian government recognises ammonia as a gaseous and vaporous inorganic substance (Category 4) under the Environmental Quality (Clean Air) Regulations 2014, in which the primary source of ammonia usually comes from intensive livestock production and industrial activity. The exploration of 2DAMP towards SDG 3 (Good Health and Well-Being), as we believe that this material advancement will lead to the creation of sustainable communities. Besides, it will contribute to comfortable environments through the provision of sensor products that consider energy and environmental conservation. In conclusion, 2DAMP is a novelty product with easy and lowcost production for the future of material sensors.